Analysis of clinical, radiographic, and treatment profile of 10 cases of neurogenic tumors and tumor-like lesions of the oral and maxillofacial region: An observational study - Mohit Mohindra; Sumit Verma; Manraj Singh Kang; Bhavneesh Goel; Anjali Pawan Kumar; Gunjan Virendra Manchanda (Wolters Kluwer Medknow Publications, 2021)
Background: Soft tissues of the head and neck areas are a very frequent site of occurrence of certain benign tumors of the peripheral nerve sheath, especially the neurofibromas. Hence, the present study was conducted for assessing clinical, radiographic, and treatment profile of 10 cases of neurogenic tumors and tumor-like lesions of the oral and maxillofacial region. Materials and Methods: Data records of a total of 10 patients who were diagnosed with tumors of neurogenic origin were enrolled in the present study. Data files were analyzed over a time period of 2 years, and complete clinical and radiographic details were evaluated. All the patients in which incomplete information was present in the record files were excluded from the present study. The assessment of the histopathologic reports was done, and final diagnosis was recorded separately in the master chart. Results: Neurofibroma was the diagnosis in two cases. In another set of two cases, final diagnosis of traumatic neuroma was achieved. A single case Schwannoma of mandible depicting multilocular radiolucency was present. Granular cell tumor was present in three cases. It was present clinically in the form of swelling, ulcerative nodule, and nodular growth in the three respective cases. Surgical excision was carried out in all the cases, and follow-up records did not depict any case of recurrence of complication posttreatment. Conclusion: Neurogenic tumors of oral and maxillafacial region are a rare phenomenon and mainly present in the form of benign neoplasm. However, careful recognition and diagnosis of these lesions are necessary to rule any possible malignant changes.